Separation and concentration of o-toluidine and tricyclazole from water with micellar enhanced ultrafiltration based on sodium dodecyl sulfate surfactant - Wu, Peng (Environmental technology, 2021)
Micellar enhanced ultrafiltration (MEUF) of o-toluidine and tricyclazole in aqueous stream using polyethersulfone (PES) hollow-fibre membrane of 6 kDa molecule weight cut-off (MWCO) and sodium dodecyl sulfate (SDS) as anionic surfactant was studied. It was found that the concentration ratio and adsorption ratio were better for the determination of the optimal pollutant or surfactant concentration than the rejection rate. The excessive dosage of surfactant had only limited effect on the separation and concentration of o-toluidine and tricyclazole but could further decrease the permeate flux. The transmembrane pressure had a significantly positive effect on the permeate flux and recovery ratio. o-Toluidine was significantly separated and concentrated by lowering the solution pH, while tricyclazole reached the best treatment efficiency in near-neutral pH condition. The sodium salts (i.e. Na2SO4, NaCl and Na2CO3) could lead to the increase in the adsorption ratio of SDS. However, Na2CO3 could result in the decrease in both the rejection rates and adsorption ratios of o-toluidine and tricyclazole. The distribution coefficient, micellar loading and micelle binding constant were evaluated to confirm the effectiveness for the MEUF treatment of these two pollutants